Supplementation of a new combination of prebiotic and postbiotic shapes fecal microbiota of old dogs while influencing immune parameters - A. Rodiles; W. Wambacq; C. Le Bourgot; E. Cox; F. Barbe; M. Hesta; E. Apper (Scientific Reports)
Abstract Healthy senior dogs were subjected for 77 days to a dietary regime with (or without) prebiotic + postbiotic mixture composed by short-chain fructo-oligosaccharides and yeast fractions (scFOS+). Their fecal microbiota was studied and the links between the microbiota and immune parameters were investigated after Lyme vaccination. All along the study results showed a clear modulation of the microbiota with a higher relative abundance (RA) for Megamonas spp., Bacteroidaceae, Bacteroidetes plebeius, Clostridiales, Phascolarctobacterium, Succinivibrionaceae, Fusobacterium spp. in feces from scFOS + dogs. An amplicon sequence variants (ASVs) index (Enterobacteriaceae + Clostridium spiroforme vs. Fusobacterium + Megamonas) was developed and found significantly different between the groups with scFOS + dogs showing a lower index suggesting a possible modulation of the physico-chemical environment in the gut, favoring the growth of strict anaerobes producing short-chain fatty acids. Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt2) analysis revealed stimulation of propionate and acetate production pathways, vitamin biosynthesis (vitamin B2, B5 and B9 precursors) and pathways related to tricarboxylic acid cycle in the scFOS + group. The RA of several ASVs from Bacteroidetes and Fusobacteria families were found moderately negatively correlated to IgA and IgG concentrations (P < 0.05). In particular, Megamonas and Phascolarctobacterium appeared as interest genera. In summary, scFOS + is a good candidate to support the health of elderly dogs through microbiota changes. Metabolomics or in vitro mechanistic experiments will be crucial to further understand the mechanisms at play.